IMPLEMENTATION OF PEER TEACHING AND RECITATION METHOD IN IMPROVING STUDENT LEARNING OUTCOMES AT SMKN 31 JAKARTA: Implementation of Peer Teaching and Recitation Method in Improving Student Learning Outcomes at SMKN 31 Jakarta - Boniarta Munte; Santi Susanti; Erika Takidah (Universitas Muhammadiyah Sorong, 2026)
Learning objectives are considered successfully met when student learning outcomes align with those objectives. These outcomes serve as a foundation for students—particularly vocational high school (SMK) graduates—as they enter the workforce. At SMKN 31 Jakarta, specifically in the Grade X Institutional Financial Accounting (AKL) class, current learning outcomes have not yet met the established objectives. This study aims to determine whether the implementation of peer teaching and recitation methods can improve student learning outcomes. The study employs the Classroom Action Research (CAR) method, utilizing the Kemmis and McTaggart model. It was conducted over two cycles, with three sessions per cycle. Data collection techniques included observation, pre-tests, post-tests, and documentation. Data analysis involved normality tests, difference tests, average scores, and pass rates. Based on the Wilcoxon difference test, the Asymp. Sig. (2-tailed) value was 0.001; since the significance value of 0.001 is less than 0.05, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Consequently, it can be concluded that the implementation of peer teaching and recitation methods effectively improves student learning outcomes.